ANALISIS LOYALITAS PETANI TERHADAP BENIH PADI UNGGUL DI KECAMATAN SEPUTIH RAMAN KABUPATEN LAMPUNG TENGAH - Titik Gustina Hutabarat; Sumaryo Gs; Suriaty Situmorang (Lampung University, 2013)
The purposes of this study were to determine the farm income which is uses the high yielding varieties seeds and analyze the loyalty of farmers to high-yielding rice varieties seeds in Seputih Raman District of Central Lampung Regency. The research sample were 74 farmers from the villages of Rama Murti, Rejo Basuki, and Rukti Endah of Seputih Raman District, in which selection was done by simple random sampling. The research data was analyzed by multiple linear regression analysis, Ordinary Least Square models, validity and reliabilitas, revenue analysis, and descriptive analysis. The results showed that profitability of rice per hectare over cash cost of Rp9,829,720.77, with R/C 2.71 and profitability per hectare on the total cost was Rp7,601,805.95, with R / C 1.95. This showed that the paddy rice farmers in Seputih Raman District provide benefits, so it is worth to be developed. The consumers / buyers could be classified as a loyal group (45.60%), neutral group (23.44%), and disloyal group (30.96%). Keywords: farming, income, loyalty, rice seeds, varieties